Greening global governance: INGO secretariats and environmental mainstreaming of IOs, 1950 to 2017 - Thomas Dörfler; Mirko Heinzel (The Review of International Organizations, 2022)
Abstract The last decades have seen a remarkable expansion in the number of International Organizations (IOs) that have mainstreamed environmental issues into their policy scope—in many cases due to the pressure of civil society. We hypothesize that International Non-Governmental Organizations (INGOs), whose headquarters are in proximity to the headquarters of IOs, are more likely to affect IOs' expansion into the environmental domain. We test this explanation by utilizing a novel dataset on the strength of environmental global civil society in proximity to the headquarters of 76 IOs between 1950 and 2017. Three findings stand out. First, the more environmental INGOs have their secretariat in proximity to the headquarter of an IO, the more likely the IO mainstreams environmental policy. Second, proximate INGOs' contribution increases when they can rely on domestically focused NGOs in member states. Third, a pathway case reveals that proximate INGOs played an essential role in inside lobbying, outside lobbying and information provision during the campaign to mainstream environmental issues at the World Bank. However, their efforts relied to a substantial extent on the work of local NGOs on the ground.
Keywords: 330; International Organizations; Environmental mainstreaming; International Non-Governmental Organizations; Policy scope; Geographical proximity; World Bank